The experience of folklore studies in traditional universities of UKRAINE 1950 – 1980s. - Vovk, Myroslava (Continuing Professional Education: Theory and Practice, 2019)
The experience of structuring folklore course content is analyzed in this article, the problems of practical lessons are characterized, the specificity of folk practices in the system of training of future teachers of classical philology at the universities of Ukraine during the Soviet period (1950 – 1980s) is investigated. The analysis of the content of the course “Folklore”, based on archival sources, which first engaged in the scientific curculation, is made; attantion is focused on the ideological bias of perspective lectures and practical training. Ideological determinism content of folklore study, impossibility of full implementation of creative approaches to understan the folklore specific in the educational process facilitated a kind of “maturation” of professional initiatives, active teachers on reform steps in the study of folklore. The internal resistance of pedagogical intelligentsia ideological pressure helped to produce a number of works on folklore literature and Slavic folklore studies, historical and folkloristic studies, a personalized approach to defining the role of scientists in the formation of folklore studies, particular importance folkloric practice, assessing student youth in research. Teachers, folklorists, whose active research and teaching activities occurred in the Soviet period, initiated the creation of departments of folklore studies at leading universities in the classic early 1990s.